Leaky bodies: masculinity and risk in the practice of cyanide fishing in Indonesia. Issue 12 (2nd December 2022) - Pauwelussen, Annet
Abstract: Dive fishing with cyanide is known as a risky fishing practice, as it pushes or lures divers to the limits of what their bodies can take. Its association with physical danger is linked to a culture of machismo and a coming-of-age process in which young men prove their bravery and become part of a shared manhood. What often remains implicit in the understanding of risk-seeking activities is the notion of body and masculinity that such practices entail and produce. Understanding risk and how it relates to masculinity in native terms requires conceptual tools to think beyond the self-contained body that navigates an external environment. Based on long-term ethnographic fieldwork in Indonesia, this article explores cyanide dive fishing in the context of risky practice in relation to the body as contingent, permeable and leaky. Drawing from situated narratives and post-human phenomenology, the article makes room for masculinities beyond the self-contained man by describing dive fishing as a transformative process of becoming fluid to a submerged world of currents and spirits. By showing how this process brings bodies to or beyond their threshold of endurance, the article sheds light on the situated vulnerabilities of dive fishers in an environment of exploitation.